Empire of deception : the incredible story of a master swindler who seduced a city and captivated the nation - Jobb, Dean, 1958- (Algonquin Books of Chapel Hill, 2015)
"It was a time of unregulated madness. And nowhere was it madder than in Chicago at the dawn of the Roaring Twenties ... Enter a slick, smooth-talking, charismatic lawyer named Leo Koretz, who enticed hundreds of people ... to invest as much as $30 million--upwards of $400 million today--in phantom timberland and nonexistent oil wells in Panama ... When Leo's scheme finally collapsed in 1923, he vanished, and the Chicago state's attorney, a man whose lust for power equaled Leo's own lust for money, began an international manhunt that lasted almost a year"--Provided by publisher.